LE SABIR CONTEMPORAIN: QUELQUES ÉLÉMENTS POUR TRADUIRE DE FRANÇAIS EN FRANÇAIS - Skorov, Pierre (Vertimo studijos, 2017)
This paper looks at the quickly spreading tendency in most European languages (with specific reference to French), whose symptoms include the proliferation of anglicisms, barbarisms, vulgarisms, systematic wrong usage, as well as rebus spelling and sms language, within the standard language. Oui, j’ai une patrie : la langue française. Albert Camus